Epigallocatechin gallate attenuates tumor necrosis factor (TNF)-α-induced inhibition of osteoblastic differentiation by up-regulating lncRNA TUG1 in osteoporosis. Issue 4 (1st April 2022) - Han, Yanfeng; Pei, Dening; Li, Wenjing; Luo, Bin; Jiang, Qingsong
ABSTRACT: Promoting osteoblast proliferation and differentiation contributes to the prevention and clinical treatment of osteoporosis. This study was to investigate the effect and mechanism of epigallocatechin gallate (EGCG) on tumor necrosis factor (TNF)-α-caused inhibition of osteoblastic differentiation. First, we cultured mouse embryo osteoblast precursor cells (MC3T3-E1) and induced by TNF-α (0, 2.5, 5, 10 ng/mL). The results revealed that TNF-α significantly inhibited the proliferation, ALP activity and mineralized nodule formation of MC3T3-E1 cells and promoted apoptosis. However, EGCG pretreatment significantly alleviated the inhibitory effect of TNF-α on MC3T3-E1. In addition, TNF-α significantly downregulated the expression of lncRNA TUG1 in MC3T3-E1, while EGCG upregulated the expression of lncRNA TUG1. After overexpression of lncRNA TUG1 in TNF-α-induced MC3T3-E1 cells, it could show similar effects as EGCG. However, interference with lncRNA TUG1 expression diminished the protective effect of EGCG on TNF-α-induced MC3T3-E1 cells. Finally, we found that EGCG inhibited TNF-α-induced activation of the Hippo/YAP signaling pathway, and that low expression of lncRNA TUG1 suppressed this effect. In conclusion, EGCG could suppress Hippo/YAP pathway activity by up-regulating lncRNA TUG1, ultimately improving TNF-α-caused inhibition of osteoblastic differentiation. GRAPHICAL ABSTRACT: uf0001